Informed Consent - Grady, Christine; Cummings, Steven R; Rowbotham, Michael C; McConnell, Michael V; Ashley, Euan A; Kang, Gagandeep (The New England journal of medicine, 2017)
An investigator obtaining informed consent traditionally asks participants to sign a written consent document — an approach that is becoming outdated. This multipart review examines electronic and video informed consent and consent in app-based and Internet-based trials, with videos showing examples. This multipart review provides an overview of innovative approaches to improving and expanding the informed consent process for researchers and participants, along with short essays covering specific areas of innovation. The Changing Face of Informed Consent Christine Grady, R.N., Ph.D. In the classic interaction in which informed consent is obtained for research, an investigator presents the potential participant with information regarding a new therapeutic, diagnostic, or prophylactic intervention and then asks the participant to read and sign a detailed written consent document. This traditional prototype is becoming outdated. Informed consent, which is ethically essential in most clinical research, respects persons’ . . .